Avaliação comparativa de segurança e eficácia na redução de odores e melhora da hidratação genital para produtos de higiene íntima - Schalka, Sérgio; Bombarda, Patrícia Camarano Pinto [UNESP]; Da Silva, Silvana Lima; Bueno, Priscila Tesini Brasil (My University, 2013)
Background and objective: It is important that women feel safe and protected against genital unpleasant odors. The aim of this study was to evaluate the safety and efficacy in reducing odors and improves genital hydration for hygiene products. Method: Study involving 230 female volunteers, age 18 to 45 years, distributed in five groups of 46 members. The volunteers used the investigational product for 30 days and the comparative for more 30 days. Between the administrations of the products, there was a wash-out period of 7 days. Each group used a different fragrance of the investigational product totaling 5 fragrances. The efficacy evaluation was subjective, through the questionnaires at the beginning and end of each treatment with product (investigational and control). Were assessed as variables, reduction of genital odour, genital moisturize, defoaming, facility of rinsing, final touch of the mucosa, final fragrance and cleaning sensation. At the end of study, a questionnaire was answered comparing directly the investigational product and control for two characteristics: odour reduction and cleaning sensation. Results: The investigational product demonstrated best ratings in all parameters, for the five fragrances, 30 days after use. With regard to product safety the volunteers had no adverse reaction. Conclusion: The care of the female genital region should be done properly promoting sense of protection and welfare of women. Hygiene should be done with products developed especially for the region intimately and with proven efficacy. © Copyright Moreira Jr. Editora.Todos os direitos reservados.
Comparative evaluation of safety and efficacy in reducing odors and improves genital hydration for hygiene products